WAIS Divide Ice-Core Chronology from Intermediate Core WDC05A - McConnell, Joseph (IEDA: US Antarctic Program Data Center, 2017)
A state-of-the-art continuous ice core analytical system was used to analyze samples from 0 to ~130 m depth of the recently collected intermediate core WDC05A from West Antarctica. Interpretation of these records and publication of findings is ongoing.